MODEL PBL BERBANTUAN QUIZIZZ MODE KERTAS PADA KONTEN BILANGAN UNTUK MENINGKATKAN KEMAMPUAN NUMERASI SISWA - Imam Wijaya; Basnawi Basnawi; Yudi Yunika Putra (Universitas Muhammadiyah Lampung, 2024)
Numeracy is part of learning mathematics and cannot be separated from everyday life. This research aims to find out how to improve numeracy skills with PBL model assisted by paper mode quizizz on number content. The research method used is class action research method. This classroom action research was carried out in two cycles consisting of planning, implementation, observation, and reflection. The subjects of this study were fifth grade students in one of the public elementary schools in Dendang District. Data collection techniques were carried out through tests, observations, and questionnaires. The test data analysis technique was carried out quantitatively using N-gain, observations using qualitative descriptive, and questionnaires quantitatively. Based on the results of the study, the PBL model with the help of using the quizizz application can improve numeracy skills in students. This is evidenced by the results of tests conducted on pretest, cycle I, cycle II, and posttest. The pretest results got an average score of 37.8, in cycle I it reached 68.9, in cycle II it reached 81.1, and experienced an increase in student posttest results with an average of 87.7. The results of the questionnaire showed that the fifth grade students of SD Negeri gave a positive response to the implementation of learning with a percentage of 97.8%. Thus, the conclusion of this study is that the PBL model assisted by the quizizz application on number content can improve numeracy skills in students. Numerasi merupakan bagian dari pembelajaran matematika dan tidak dapat dipisahkan dari kehidupan sehari-hari. Penelitian ini bertujuan untuk mengetahui bagaimana meningkatkan kemampuan numerasi dengan model PBL berbantuan quizizz mode kertas pada konten bilangan. Metode penelitian yang digunakan adalah metode penelitian tindakan kelas. Penelitian tindakan kelas ini dilaksanakan dalam dua siklus yang terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Subjek dari penelitian ini adalah siswa kelas V di salah satu SD Negeri di Kecamatan Dendang. Teknik pengumpulan data dilaksanakan melalui tes, pengamatan, dan kuisioner. Teknik analisis data tes dilakukan secara kuantitatif menggunakan N-gain, pengamatan menggunakan deskriptif kualitatif, dan kuisioner secara kuantitatif. Berdasarkan hasil penelitian, model PBL dengan bantuan penggunaan aplikasi quizizz dapat meningkatkan kemampuan numerasi pada siswa. Hal tersebut dibuktikan melalui hasil tes dilakukan pada pretest, siklus I, siklus II, dan posttest. Hasil pretest mendapat nilai rata-rata 37,8, pada siklus I mencapai 68,9, pada siklus II mencapai 81,1, dan mengalami kenaikan hasil posttest siswa dengan rata-rata 87,7. Adapun hasil kuisioner menunjukkan siswa kelas V SD Negeri memberikan respons positif terhadap pelaksanaan pembelajaran yakni persentase sebesar 97, 8%. Dengan demikian, kesimpulan dari penelitian ini adalah model PBL berbantuan aplikasi quizizz pada konten bilangan dapat meningkatkan kemampuan numerasi pada siswa.